Evaluation of Health Literacy in Children and Adolescents in The South Bohemian Region, CZ, Using the Standardized HLSQ16 Questionnaire - Machová, Alena; null, null; Nováková, Dita (STEF92 Technology Ltd., 2018)
This article introduces the results of quantitative research focused on the assessment of the health literacy of children and adolescents in the South Bohemian region.
Hodnocení zdravotní gramotnosti dětí a adoelscentů Jihočeského kraje, ČR, s využitím standardizovaného dotazníku HLSQ16.
Keywords: Evaluation; Health Literacy; Children; Adolescents; Standardized; HLSQ16 Questionnaire; Hodnocení; zdravotní gramotnost; děti; adolescenti; standardizovaný dotazník HLSQ16.